RECOGNITION OF ILLEGITIMATE CHILDREN IN VARIOUS LAWS IN INDONESIA - Yunanto Yunanto (Diponegoro Law Review, 2017)
In any regulations in Indonesia, there are differences in the inherent status and rights between legitimate and illegitimate children. Consequently, it surely affects the relationship between the children and their parents. Illegitimate children only have the civil relationship with their mothers. In order that the illegitimate children have a certain relationship with their biological fathers, it requires a legal action in the form of the recognition of biological father. However, there are legal ambiguities in the regulations that govern the institution of the recognition of children as stated in the Indonesian Civil Code, Law No. 23 of 2006 in conjunction with Law No. 24 of 2013, and the Decisions of the Constitutional Court No. 46/ PUU-VIII/ 2010 as a corrective provision to the Marriage Law (UUP), and the Islamic Law Compilation (KHI). The legal effects are: the discrimination derived from legal injustice and certainty in the implementation of the child recognition.